Becoming Superman : my journey from poverty to Hollywood with stops along the way at murder, madness, mayhem, movie stars, cults, slums, sociopaths, and war crimes /: my journey from poverty to Hollywood with stops along the way at murder, madness, mayhem, movie stars, cults, slums, sociopaths, and war crimes. ([2019]) - Straczynski, J. Michael, 1954-
No abstract available